Studies on Collector-Free Flotation Kinetics of Talc and Chalcopyrite - Bai Limei; Han Yuexin; Yuan Zhitao; Ma Yuxin; Niu Fusheng (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
"Using batch flotation experiment, contact angle measurement, particle size analysis, and scanning electron microscope (SEM), the influence and difference of pH value on the flotation rate of talc and chalcopyrite were investigate without collector at the pH range of 3~11. The results showed that, the flotation rate of talc decrease with the increasing of flotation time, while that of chalcopyrite hardly affect by flotation time, besides, the flotation rate of chalcopyrite is much less than that of talc, so the laws of flotation rate of the two minerals are independent of pH value. The flotation test data of two minerals are simulated with first order and multi-rate flotation kinetic model respectively. The simulation results showed that flotation of talc only meet the first order kinetic model, while chalcopyrite’s meet the both. In addition, According to test results of talc and chalcopyrite by the particle size distribution, SEM photographs and the contact angle measurement, the reason why talc did not conform to the first order kinetic model is not because of particle size distribution, but of particle shape. That is to say, because of sheet structure of talc, the contact angle of layers and sections are 74°and 52°respectively. At the same time, the contact angle of layers and sections are different between the particles. So flotation rates between talc particles are difference.INTRODUCTIONPossessing superior self-induced, collector-induced and sulfur-induced floatability, chalcopyrite exhibits good floatability at a wide range of pH values and potentials. Serpentine are regarded as the most difficult selected type in various chalcopyrite ore, and the predominant reason is that it contains talc. Talc, as a nonpolar layered silicate mineral, is one kind of common associated mineral in sulfide ores (Lu, 2010). Concentrate quality and flotation process of chalcopyrite are influenced as a result from the presence of talc. It is because that talc has inherent floatability which makes it readily mixed with the floated mineral and talc is easy to slime causing the slime coating of the valuable mineral (Beattie et al., 2006). Thus in order to improve the flotation effect of chalcopyrite, methods can be introduced from two respects. One method is that fast-floating talc mineral is floated preferentially, and the other is that sulfide mineral is floated prior to talc by depressing the flotation of talc mineral (Beattie et al., 2006), nevertheless, no matter with which the flotation effect of fine-sized chalcopyrite is not positive. Therefore, in order to realize the flotation separation of talc and chalcopyrite, the difference between the inherent floatability of fine-sized chalcopyrite and talc is researched and analyzed in terms of flotation dynamics in the absence of collector and frother."